2021
DOI: 10.1016/j.sjbs.2021.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of electronic properties, radical scavenging activity and QSAR of oxadiazole derivatives by molecular docking and first-principles approaches

Abstract: Eight new oxadiazole derivatives were designed then geometries for ground state were optimized through Density Functional Theory (DFT) at B3LYP/6-31G** level. Single electron transfer mechanism has been studied to understand the antioxidant ability of the oxadiazole derivatives. Then molecular electrostatic potential and quantitative structure–activity relationship (QSAR) was probed. Additionally, we shed light on different molecular descriptors, e.g., electrophilicity(ω), electronegativity(χ), electrophilicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It is known that the structure–activity relationship models for understanding the biological activity and toxicity of molecules may be generated in terms of global and local reactivity descriptors within a conceptual density functional theory framework [ 64 ]. The global reactivity indexes of studied compounds were estimated based on the one-electron energies of the frontier molecular orbitals (FMO) [ 65 , 66 ]. The calculated molecular descriptors and the relationships between them for studied compounds as well as biological activities are summarized in Table 8 .…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the structure–activity relationship models for understanding the biological activity and toxicity of molecules may be generated in terms of global and local reactivity descriptors within a conceptual density functional theory framework [ 64 ]. The global reactivity indexes of studied compounds were estimated based on the one-electron energies of the frontier molecular orbitals (FMO) [ 65 , 66 ]. The calculated molecular descriptors and the relationships between them for studied compounds as well as biological activities are summarized in Table 8 .…”
Section: Resultsmentioning
confidence: 99%
“…The best anti-free radical activity is attributed to the compound 5-DPSS with an EC 50 value of 7.10 ± 3.2 μg/mL, while the weak activity is recorded for the product 5-DPM (20.97 ± 0.89 μg/mL). The percentage inhibition of the DPPH• increases with increasing concentration in a dependent manner, either for the Schiff base compounds or for standards [33][34][35]. The inhibition efficiency of synthesized compounds was found to be in ascending order of 5-DPM < 3-DPSS < 3-DPS < 3-DPM < 5-DPS < 5-DPSS (Fig.…”
Section: Dpph• Scavenging Activitymentioning
confidence: 85%
“…Several studies have demonstrated the antioxidant potential of the hydrazide-hydrazones moiety. 15,16 Implementing electron donating groups has also been discussed as a potential technique for enhancing the overall antioxidant properties. 17 In addition, research papers have described good antioxidant capacities of the pyrrole moiety, with particular attention given to the multi-functionalized pyrrole rings.…”
Section: Design and Synthesis Of Pyrrole Analoguesmentioning
confidence: 99%